2015
DOI: 10.1016/j.ajog.2014.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the oxidative stress hypothesis in diabetic embryopathy through proapoptotic kinase signaling

Abstract: Maternal diabetes-induced birth defects occur in 6-10% of babies born to mothers with pregestational diabetes, representing a significant maternal-fetal health problem. Currently, these congenital malformations represent a significant maternal-fetal medicine issue, but are likely to create an even greater public health threat as 3 million women of reproductive age (19-44 years) have diabetes in the United States alone, and this number is expected to double by 2030. Neural tube defects (NTDs) and congenital hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 150 publications
(161 reference statements)
4
85
0
1
Order By: Relevance
“…Both oxidative stress and ER stress converge on the induction of aberrant apoptosis, a hallmark of diabetic embryopathy[10, 11, 30, 34]. Previous work by Chen et al demonstrated that punicalagin can protect human trophoblasts from stress-induced apoptosis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Both oxidative stress and ER stress converge on the induction of aberrant apoptosis, a hallmark of diabetic embryopathy[10, 11, 30, 34]. Previous work by Chen et al demonstrated that punicalagin can protect human trophoblasts from stress-induced apoptosis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Maternal diabetes induces oxidative stress in the developing embryo (6,9,26,45,48,53,58,59) and activates apoptosis signal-regulating kinase 1 (ASK1), a mitogen-activated protein kinase (MAPK) kinase, in neurulation stage embryos (47,57). ASK1 responds to oxidative stress and induces apoptosis via the activation of c-Jun NH 2 -terminal kinase 1/2 (JNK) and/or p38 MAPK (42).…”
mentioning
confidence: 99%
“…Apoptosis has been hypothesized as a primary mechanism of diabetes-induced birth defects 5759 . Under euglycemic conditions, very low basal levels of apoptosis are observed in the embryonic tissues during organogenesis (E7-E11) 60 .…”
Section: Molecular Intermediates and Signaling Pathways Contribute Tomentioning
confidence: 99%
“…However, the apoptotic mechanism in this disease process is not well understood. Evidence from clinical and experimental studies has revealed that maternal diabetes leads to an imbalance in intracellular reduction-oxidation (redox) homeostasis, resulting in intracellular oxidative stress 5759,6770 . Recent studies have demonstrated that oxidative stress and ER stress are the main biochemical and molecular mechanisms underlying maternal diabetes- induced apoptosis 66,7175 .…”
Section: Molecular Intermediates and Signaling Pathways Contribute Tomentioning
confidence: 99%
See 1 more Smart Citation